A systematic review and classification of interventions for speech‐sound disorder in preschool children. Issue 3 (16th January 2018) - Wren, Yvonne; Harding, Sam; Goldbart, Juliet; Roulstone, Sue
Abstract: Background: Multiple interventions have been developed to address speech sound disorder (SSD) in children. Many of these have been evaluated but the evidence for these has not been considered within a model which categorizes types of intervention. The opportunity to carry out a systematic review of interventions for SSD arose as part of a larger scale study of interventions for primary speech and language impairment in preschool children. Aims: To review systematically the evidence for interventions for SSD in preschool children and to categorize them within a classification of interventions for SSD. Methods & Procedures: Relevant search terms were used to identify intervention studies published up to 2012, with the following inclusion criteria: participants were aged between 2 years and 5 years, 11 months; they exhibited speech, language and communication needs; and a primary outcome measure of speech was used. Studies that met inclusion criteria were quality appraised using the single case experimental design (SCED) or PEDro‐P, depending on their methodology. Those judged to be high quality were classified according to the primary focus of intervention. Outcomes & Results: The final review included 26 studies. Case series was the most common research design. Categorization to the classification system for interventions showed that cognitive–linguistic and production approaches to intervention were the most frequently reported. The highest graded evidence was for three studies within the auditory–perceptual and integrated categories. Conclusions & Implications: The evidence for intervention for preschool children with SSD is focused on seven out of 11 subcategories of interventions. Although all the studies included in the review were good quality as defined by quality appraisal checklists, they mostly represented lower‐graded evidence. Higher‐graded studies are needed to understand clearly the strength of evidence for different interventions.